Construction joints in substandard beam–column connections subjected to cyclic loading. Issue 8 (21st January 2019) - Roy, Biswajit; Laskar, Aminul Islam
Abstract : Construction joints in columns are inevitable in multi-storey reinforced-concrete structures. However, little research on assessing the performance of beam–column connections with construction joints in columns has been reported. The work reported in this paper was an attempt towards evaluating the performance of substandard beam–column connections with a construction joint in the column. Six beam–column joint test specimens, with and without a construction joint in the column, were prepared using mild steel rebars and were subjected to cyclic loading. The test results showed that the presence of the construction joint in the column had little influence on the cyclic performance of the test specimens. Instead, the specimens failed due to inadequate detailing of the beam–column connections.